Thai diabetes prevention education program: development and validation of the Thai physical activity questionnaire for at-risk people - Maenum Chirdkiatisak (2020)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Aim: This study aimed to develop and validate the Thai physical activity questionnaire (Thai-PAQ) for Thai people at risk for type 2 diabetes (T2D). Subjects and methods: After development and validation of the questionnaire, 95 people at risk for T2D were recruited. The Thai-PAQ was developed based on the International-PAQ. The Thai-PAQ was evaluated by three experts to ensure content validity. The at-risk people were interviewed using the Thai-PAQ for the previous 7 days’ activities. Spearman’s correlation was used to compare the accelerometer and Thai-PAQ for concurrent validity. Interclass correlation was used to evaluate the reliability of the Thai-PAQ separated by 3 days. Chi-square test was used to represent significant differences (p < 0.05) in the proportion of participants meeting the current physical activity guidelines. Results: The content validity of the Thai-PAQ was 0.91. The total physical activity from the Thai-PAQ (MET-min week−1), which included the part-time occupation domain and excluded the part-time occupation domain, was significantly correlated with the total physical activity (counts week−1) according to the ActiGraph accelerometer (r = 0.57 and 0.54, p < 0.01, respectively). The 3-day test-retest reliability of the total physical activity of the developed PAQ was 0.86 (p < 0.05) when including the part-time occupation domain and was 0.85 (p < 0.05) when excluding the part-time occupation domain. Conclusions: The study showed that that concurrent validity had high correlation compared with the ActiGraph accelerometer. Reliability was also acceptable as high reliability. The Thai-PAQ is considered useful for communities as well as a means to ultimately promote physical activity in communities.